a prescription for consent - Marina Tsaplina; Charlee Huffman (maxp (Disability Studies Quarterly, 2022)
No abstract available.
Keywords: Indigeneity; whiteness; anticolonial; poetic knowledge; Glissant; relation; consent; biomedicine; bioethics